Native American women with infants, Dawson, Yukon, ca. 1899 - Hegg, Eric A., 1867-1948
Three women bundled up for the weather, 2 with infants in blankets on their backs, ca. 1898-1900. Posed sitting on logs, in front of log buildings. Caption on image: Hegg & Co. Squaws and their papooses at Dawson Y.T.